Evaluation of Ethics Curricula and Faculty in Accredited Undergraduate Radiologic Technology Programs. - Prier, Janyce; Ayars, Candace (Radiation Therapist)
Purpose To investigate the state of ethics curricula in accredited undergraduate radiologic technology programs. Methods A causal-comparative research design was used to collect and analyze data about faculty degrees, their knowledge of the Realm-Individual Process-Situation (RIPS) Model of Ethical Decision-Making, the degree level offered, and the ethics curriculum. Postprimary certification programs and applicant programs for accreditation were excluded. Results Analysis was conducted on 226 completed surveys. The findings showed a significant association between teaching strategies and program degree (P = .001) and assessment strategies and faculty degree (P = .006). However, no significant association existed between assessment strategies and program degree (P = .070), ethical course content and program degree (P = .122), teaching strategies and faculty degree (P = .159), or ethics course content and faculty degree (P = .558). Discussion Study findings showed reliance of faculty on lectures to present ethical content, tests to assess student understanding, and teaching using the American Registry of Radiologic Technologists Standards of Ethics. A small number used other methods such as case-based studies, group discussions, and other ethical theories. The high variance in responses showed a need for a structured ethics curriculum. Conclusion In accredited radiologic technology programs, the methods for teaching ethics and assessment techniques might be related to the level of the degree being offered and the education of the instructing faculty member, respectively. These findings demonstrate a need for developing a standardized ethics curriculum in these programs.